2019
DOI: 10.1182/blood-2019-123253
|View full text |Cite
|
Sign up to set email alerts
|

Middle East Respiratory Syndrome (MERS) Infection in Hematological and Oncological Patients: A Case Series from a Tertiary Care Center in Saudi Arabia

Abstract: We present the largest to date of a case series of nine patients with hematological and oncological malignancies who were infected with Middle East Respiratory Syndrome Coronavirus (MERS-CoV). MERS-CoV is a novel beta-coronavirus with a high fatality rate in comorbid patients. The majority of MERS cases globally were reported from Saudi Arabia (1983 cases, including 745 related deaths with a case-fatality rate of 37.5%) according to the WHO update of February 2019. All were clinically stable before acquiring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Despite a lower-case fatality rate, the total number of deaths due to COVID-19 has outweighed that due to MERS and SARS due to the greater number of cases. Referring to oncology, cancer patients had a dismal outcome during the previous viral outbreaks [11][12][13]. As a group, cancer patients are vulnerable and have compromised overall health, and on anticancer drugs that also suppress the immune system.…”
Section: Learning From Previous Outbreaksmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a lower-case fatality rate, the total number of deaths due to COVID-19 has outweighed that due to MERS and SARS due to the greater number of cases. Referring to oncology, cancer patients had a dismal outcome during the previous viral outbreaks [11][12][13]. As a group, cancer patients are vulnerable and have compromised overall health, and on anticancer drugs that also suppress the immune system.…”
Section: Learning From Previous Outbreaksmentioning
confidence: 99%
“…As a group, cancer patients are vulnerable and have compromised overall health, and on anticancer drugs that also suppress the immune system. For instance, Alaskar et al reported a 100% mortality upon acquiring MERS in their case series of nine patients with cancer [11].…”
Section: Learning From Previous Outbreaksmentioning
confidence: 99%
“…Four of the six studies of MERS examined patients with cancer in Saudi Arabia (21)(22)(23)(24), and one case report from Germany described a case of a patient from the United Arab Emirates (25). Only one study examined the 2015 Korean MERS outbreak (26).…”
Section: Mers (Mers-cov)mentioning
confidence: 99%
“…Also, the two refractory cases had evidence of co infection with enterococcus and gram negative bacteremia. 18…”
Section: Evidences Of Relapse and Reinfection Of Sars And Mersmentioning
confidence: 99%